(untitled) (Fiep Bulletin - online, 2017)
The ludicidade is very important tool of education, Through it you can develop the most varied subjects anddisciplines, and should be present in the methodology of every teacher. It is necessary that the ludicidade is present on the day today schools, so that the content to be streamed from fun way without losing the efficiency in the absorption of information. Theplay is increasingly important in the development of children, especially during the child education where the teacher of physicaleducation can use as a tool for teaching and learning. To portray such importance relataremos the lived experience during theDiscipline Motor Learning, while academics from the 4th period of the course of Bachelor of Physical Education from theUniversity of Amazonas State in the city of Manacapuru, Amazonas State, Brazil. The experience came from the opportunity tolead to a school of the municipal school network of the city of Cedar Creek the project planner of leisure, which involved childrenfrom 5 different classes, with activities to develop the motor aspects and cognition through an approach entirely based in theuniverse of fun super heroes.